비전형적인 하라다병 3예 - 양지욱; Ji Wook Yang; 오태훈; Tae Hoon Oh; 박영훈; Young Hoon Park (Daihan angwa haghoi jabji, 2009)
목적: 전형적인 양상을 보이지 않는 하라다병 3예를 경험하였기에 보고하는 바이다. 증례요약: (증례 1) 56세 남자가 좌안에 삼출망막박리를 동반한 전형적인 하라다병 소견을 보였으나 4년간 우안에는 발병하지 않았다. (증례 2) 73세 남자가 두통과 이명 등을 동반한 양안 시력 감소를 주소로 내원하여 시행한 안저검사상 양안의 윤상맥락막박리만 관찰되고 삼출망막박리는 보이지 않았으며 이후 재발 시에도 윤상맥락막박리만 관찰되었다. (증례 3) 53세 여자가 심한 두통과 이명을 동반한 양안의 시력 감소를 주소로 내원하여 실시한 안저검사상 심한 맥락막주름만 관찰되었고 이후 2회 재발에서도 맥락막주름이 특징적이었다. 결론: 저자들은 전형적인 하라다병의 특징인 양안의 삼출망막박리를 보이지 않는 증례를 경험하였기에 보고하며 하라다병이 다양한 양상으로 관찰될 수 있음을 숙지해야 할 것으로 생각된다. <대한안과학회지 2009:50(1):160-166> Purpose: We present three cases of atypical Harada`s disease that exhibited different clinical courses. Case summary: (Case 1) A 56-year-old male initially presented with typical findings of Harada`s disease accompanied by exudative retinal detachment of the left eye. However, he did not show any signs and symptoms of Harada`s disease in his right eye for 4 years. (Case 2) A 73-year-old male came to our clinic complaining of decreased visual acuity in both eyes with headache and tinnitus. Fundoscopic findings showed bilateral annular choroidal detachment but no evidence of exudative retinal detachment. The same result was obtained on remission. (Case 3) A 53-year-old female presented with decreased visual acuity in both eyes with headache and tinnitus. Fundoscopic findings showed severe choroidal folds instead of exudative retinal detachment, which was observed in 2 other remissive cases. Conclusions: We report 3 cases of atypical Harada`s disease that did not present with bilateral exudative retinal detachment. Ophthalmologists should know that Harada`s disease can exhibit diverse clinical courses. J Korean Ophthalmol Soc 2009;50(1):160-166